Sentidos del trabajo derivados de las experiencias laborales en personas en situación de discapacidad laboral (2015)
This paper presents the description of ways of working that are derived from the work experiences in people experiencing visual impairment. For this research (open) qualitative interview was conducted three people in condition of visual impairment, collecting stories about their experiences in relation to work. The research presents a qualitative approach with descriptive scope; data processing was performed using content analysis. The research observed speech elements that show the construction of meanings related to the work experience. It is relevant to investigate this issue since studies with people with disability are given in the order of inclusion and exclusion in different social activities. It is very important to provide knowledge in the field of psychology with regard to the construction of meanings that these people make work and work. For this were taken as referring Renteria Garcia, Restrepo, Riascos with text senses work from paths and personal resources to face the world of work.